Pengaruh Profitabilitas, Likuiditas, Dan Kualitas Aset Terhadap Stabilitas Keuangan Bank Bjb Syariah Periode 2015-2024 - Wida Zulfa Fitriya; Nur Eka Setiowati; Layaman (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
The importance of financial stability in maintaining a bank's financial performance and minimizing the risk of financial distress and bankruptcy necessitates an analysis of its influencing factors. This research is motivated by the occurrence of systemic risk at BJB Syariah Bank, which is the main cause of financial stability disruption based on Bank Indonesia Regulation No. 16/11/PBI/2014. This study aims to analyze profitability (ROA), liquidity (FDR), and asset quality (NPF) on the financial stability of BJB Syariah Bank. The research method uses a quantitative approach with secondary data in the form of quarterly financial reports for the 2015-2024 period analyzed through multiple linear regression. The results show that profitability has a significant positive effect on financial stability, while liquidity and asset quality have no partial effect. Simultaneously, all three variables influence the financial stability of BJB Syariah Bank. This finding implies that increasing profitability is a key factor in maintaining the financial stability of BJB Syariah Bank.